The influence of land management and seasonal changes in surface vegetation on flood mitigation in two UK upland catchments. Issue 12 (1st December 2022) - Bond, Stephanie; Willis, Thomas; Johnston, Jean; Crowle, Alistair; Klaar, Megan J.; Kirkby, Mike J.; Holden, Joseph
Abstract: As the frequency and magnitude of storm events increase with climate change, understanding how season and management influence flood peaks is essential. The influence of season and management of grasslands on flood peak timing and magnitude was modelled for Swindale and Calderdale, two catchments in northern England. Spatially‐Distributed TOPMODEL was used to investigate two scenarios across four storm events using empirically‐based soil and vegetation data. The first scenario applied seasonal changes in vegetative roughness, quantifying the effect on flood peaks at catchment scale. The second scenario modelled the influence of grassland management from historical high‐intensity grazing to a series of natural succession stages between grassland and woodland, and a conservation‐based management. Model outputs were analysed by flow type, measuring total, overland and base flow peaks at the catchment outlet. Seasonal changes to vegetation were found to increase overland flow peaks by up to +2.2% in winter and reduce them by −5.5% in summer compared to the annual average. Percentage changes in flood peak due to hillslope grassland management scenarios were more substantial; overland flow peaks were reduced by up to 41% in Calderdale where extensive woodland development was the most effective mitigation strategy, and up to 35% in Swindale, where a rank grassland dominated catchment was the most effective. Conservation‐based farming practices were also useful, reducing overland flow peak by up to 42% compared to the high intensity grazing scenario. Neither management nor seasonality changed the timing of runoff peaks by >45 min. Where overland flow dominates, especially in catchments with shallow soils, surface roughness was found to be more influential than soil permeability for flood mitigation. We recommend that seasonal changes to roughness are considered alongside the spatial distribution of Natural Flood Management in mosaiced upland catchments. Abstract : Modelling flow peaks and timing in response to seasonal vegetation change and applied grassland management from high‐intensity grazing, through natural succession to woodland, and conservation farming.